Modules design of basic english for electronics technicians developed at cea (centro de estudios aeronauticos) educative english modules based on pedagogic tasks (2006)
As a requirement of a new era where we are facing scientific and technological advances, our country needs urgently to develop an educational process, in which everybody achieves a good management of one or more foreign languages in order to have an equality of bilingual conditions that are going to facilitate our participation as Colombian members in the global culture without loosing the sense of our own identity. The Colombian Civil Aeronautics is not outside of this demand and, as a part of a big entity as the ICAO (International Civil Aeronautic Organization), they need to follow the international parameter that this entity has established about the use of English as a unique language in this field, for this main reason in the following paper, you are going to observe how through the design of five modules of basic English for an specific area of Colombian aeronautics workers, the CEA (Centro de Estudios Aeronáuticos) as the group in charge of the educational space in the Colombian Civil Aeronautics continued a process of teaching English through different resources designed exclusively to cover their necessities, with the support of English teachers from Universidad Distrital. First of all we described in detail the problem mentioned above and why we were inspired to design material in order to contribute in the solution of this situation, at this point we established some goals to achieved based on theoretical statements proposed mainly by Nunan, Tomlinson and previous works developed by other students in our university, on the other hand we present the type of study that we followed in the design of this material, how it was designed and used by the population at the CEA, taking into consideration the people and resources involved in this work, also we include the structure of each module with their own technical requirements for use and installation, finally we have the findings and results of the evaluation that the population gave of the material in order to conclude this written response of our work in the internship at CEA.